Are adults in need of support and protection being identified in emergency departments?. Issue 1 (8th February 2016) - Jarvis, Alison; Fennell, Kate; Cosgrove, Annette
Abstract : Purpose: – Frequent attendance at emergency departments (ED) has been identified in adult protection reviews as a potential warning sign of the escalation of someone's vulnerability. Concern has been expressed about the engagement of the National Health Service (NHS) in adult protection and the small number of NHS adult protection referrals. More specifically ED departments have been identified as an area of high patient through put where there has been little evidence around how well adult support and protection (ASP) was being delivered. The paper aims to discuss these issues. Design/methodology/approach: – A series of audits were undertaken in three different hospitals across a large Scottish Health Board accessing ED at different times of day on different days of the week to test out whether NHS staff working in EDs are identifying adults who meet the criteria of "an adult at risk". Findings: – The audits identified a total of 11 patients from a total sample of 552 records examined who may have met the criteria to be considered an adult at risk, although further information would have been required to make a fully informed decision. Research limitations/implications: – The main study limitation is that the hospitals are all within a single Health Board. The EDs have a large number of admissions and it is possible that a less pressurised area, might have a lower threshold of "risk" than the practitioners involved in the audits. The decision as to whether an adult was considered to meet the three-point test by the three people undertaking the audit was dependent on the quality of information recorded on the patients' electronic hospital record. Practical implications: – It is essential that NHS Boards proactively support practice in ED settings so staff are able to identify adults at risk of harm under the ASP legislation so that ED staff are responsive to ASP needs. Originality/value: – The research evidence around adult protection in the UK is still emerging. The development of good practice based on the Scottish Government's ASP legislation is still being shaped. In England and Wales, the principles of identification and multi-agency working underpinning the safeguarding of vulnerable individuals are broadly similar to Scotland. These audits add to the literature by challenging the assumption that patients who would benefit from local authority investigation and possible support are not being identified within EDs.